ANALISIS EFEKTIVITAS PROGRAM WORK FROM HOME (WFH) BERBASIS OUTCOME MASA PANDEMI COVID-19 - Lindawati Kartika; R Dikky Indrawan; Roni Jayawinangun (UNIVERSITAS INDRAPRASTA PGRI, 2021)
The term Work from home (WFH) has become increasingly popular after the Covid-19 spread occurred in various parts of the world, including in Indonesia. The implementation of work from home simultaneously in various companies is something new in Indonesia. Therefore it is necessary to investigate the factors of work from home implementation to determine the effectiveness of outcome-based telework. This research uses the descriptive analysis method and Structural Equation Modeling-Partial Least Square (SEM-PLS). The type of data used in this research is quantitative by using primary data in the form of direct interviews and filling out questionnaires to the employees or professional workers in Indonesia who work by telework/ work from the home program during the pandemic of Covid 19 situations. Secondary data gathered from literature studies and previous research. The results of this study indicate that five variables have a significant influence, namely the possibility to work from home because of the type of work, possession to work during the most productive time, suitability of a working place at home, time efficiency, and team member support. The suitability variable of a working place at home has the most significant influence compared to other variables.